Anticancer ethnomedicines for cancer treatment in Taiwan - Ko, Chien-Yu; Chi, Min-Han; Chao, Jung; Huang, Shyh-Shyun; Lee, Hong-Zin (Frontiers in Pharmacology, 2025)
IntroductionCancer remains a leading global health issue and has been the leading cause of death in Taiwan for over four decades. In recent years, ethnomedicines have gained growing attention as complementary therapies in cancer treatment. However, systematic investigations linking traditional medicinal practices with cancer remain limited. This study aims to explore the types, preparation methods, and parts used of anticancer ethnomedicines and cancer types across different regions in Taiwan through ethnobotanical surveys, and to preserve and transmit traditional knowledge.MethodsData were collected through questionnaire-based interviews with 210 participants, sampled proportionally by region, age, gender, and education based on national demographics.ResultsChi-squared tests showed that only education level significantly influenced the number of anticancer ethnomedicines mentioned (p < 0.001), suggesting that Taiwan’s policies promoting traditional medicine education may enhance knowledge retention. A total of 159 ethnomedicines were mentioned, with 146 plant species classified into 66 families, predominantly Asteraceae, Lamiaceae, and Fabaceae. The most commonly used plant parts were whole herba for herbaceous species, herba and radix for lianas, and leaves for trees and shrubs. Water decoction was the most frequently reported preparation method. The top ten mentioned ethnomedicines were traditionally used for a broader range of cancers than reported in the PubMed literature, especially for breast, lung, liver, and colorectal cancers, showing high consistency between traditional usage and modern scientific findings. Consensus factor analysis revealed high agreement among respondents regarding remedies for the ten most common cancers in Taiwan, except for prostate and oral cancers, possibly due to clinical treatment limitations or low questionnaire response rate. Taiwan’s cultural diversity, linguistic unity, and unique geographical environment facilitate the accurate and comprehensive collection of ethnomedicinal data, leading to more valuable research outcomes.DiscussionIn summary, the results of this study provide a valuable foundation for future anticancer research, serving as a priority focus for further investigation into the underlying mechanisms of anticancer activity. Moreover, this research supports the scientific development and potential drug discovery of ethnomedicines in modern cancer treatment, contributing to the integration of traditional knowledge with contemporary biomedical approaches.